Faktor Pelayanan Publik, Informasi Perpajakan Dan Kepatuhan Wajib Pajak dalam Meningkatkan Kesadaran Masyarakat Membayar Pajak - Permenas Djaha; Ni Luh Putu Sri Purnama Pradnyani (JEMAP, 2019)
This research is about public service factors, taxation information and taxpayer compliance in increasing public awareness of paying taxes in Tabanan Regency for the 2013-2017 period. Data collection techniques used were questionnaires and documentation. The number of respondents selected in this study were 100 people who are taxpayers who pay taxes to the Tabanan Primary Tax Service Office. The data analysis technique used was factor analysis. The tax awareness factor has an eigen value of 3.892% with a variant percentage value of 19.462%, a tax service factor has an eigen value of 10.967% with a percentage of variance of 54.837%. The tax information factor has an eigen value of 1.674% with a variance of 8.337% while the tax compliance factor with an eigen value of 1.474% with a variance of 7.367%. From the results of data analysis, the most dominant factor influencing public awareness in paying taxes was the tax service. Therefore the Tabanan Primary Tax Service Office employees had to continue maintaining and more improving their service quality  to taxpayers.